Voicing Change: A Comparative Reading of Selected Works by Pramoedya Ananta Toer and Katharina Susannah Prichard - Puspita, Ida (Universitas Ahmad Dahlan, 2015)
Although coming from different historical and political backgrounds, Indonesian Pramoedya Ananta Toer and Australian Katharina Susannah Prichard both have used their writing to rehearse their concerns with the social and political situations in their respective societies. In The Girl from the Coast (1987) and Coonardoo (1929), they create the setting for a staging of the effects of colonial, racial and gender ideologies on the lives of marginalised and oppressed individuals. Through the characters of The Girl and Coonardoo respectively Pramoedya and Prichard hold up a lens to an awakening concern with minorities in specific periods in Indonesian and Australian societies. The novelsâ main female characters serve thus as spokespersons for an agenda of social and political change that characterise the work of Pramoedya and Prichard.Â Â Â This paper will examine how these two novels depict marginalised groups in Indonesia and Australia and the significant role these groups play in both challenging and sustaining a national memory. To this extent it is concerned with how they are positioned as well as how they position themselves in the patriarchal and colonial societies of the late 19th and early 20th centuries. Pramoedyaâs and Prichardâs shared perspectives on political and social matters lead to some comparable aspects in the way they depict the social dynamics in the texts. Readers are led to see the tensions between identity and class/race and family and nation through the eyes and the voices of the marginalised women characters.Â Keywords: comparative literature, voicing change, Pramoedya, Prichard